2018
DOI: 10.1097/gme.0000000000001126
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor symptoms in women over 60: results from the Data Registry on Experiences of Aging, Menopause, and Sexuality (DREAMS)

Abstract: A substantial number of women seen in a specialty menopause clinic were over age 60 years and reported msVMS, highlighting that VMS may be disruptive in women over a decade past the natural age of menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Many women continue to report vasomotor symptoms beyond age 60, with over 40% of women aged 60 -65 reporting moderate to severe VMS (13,109). For those women with persistent bothersome symptoms, a discussion about benefits of HT relief vs risks associated with continuing HT beyond age 60 is warranted.…”
Section: Persistent Symptomsmentioning
confidence: 99%
“…Many women continue to report vasomotor symptoms beyond age 60, with over 40% of women aged 60 -65 reporting moderate to severe VMS (13,109). For those women with persistent bothersome symptoms, a discussion about benefits of HT relief vs risks associated with continuing HT beyond age 60 is warranted.…”
Section: Persistent Symptomsmentioning
confidence: 99%
“…Approximately 60% to 80% of women experience VMS during the menopause transition, 1,2 which averages 7 to 9 years, although some continue to have VMS in their 70s and 80s. [2][3][4][5] These symptoms can be associated with a decrease in quality of life, often manifested as sleep disturbance, depression, and even mental exhaustion. [1][2][3][4][5][6] Demographic and socioeconomic factors can affect VMS frequency and intensity.…”
Section: ■ the Epidemiology Of Vasomotor Symptomsmentioning
confidence: 99%
“…[2][3][4][5] These symptoms can be associated with a decrease in quality of life, often manifested as sleep disturbance, depression, and even mental exhaustion. [1][2][3][4][5][6] Demographic and socioeconomic factors can affect VMS frequency and intensity. The Study of Women Across the Nation 7 revealed that Black women have the highest prevalence REVIEW…”
mentioning
confidence: 99%
“…The BEERS Criteria are also applied to the use of low-dose vaginal estrogen therapies for treatment of GSM despite the fact that systemic absorption is minimal with vaginal inserts, tablets, and rings, 23 and the use of these products is not associated with long-term adverse events in observational studies 46,47 . In addition, vasomotor symptoms commonly persist beyond the age of 60 years, and GSM symptoms tend to worsen rather than improve over time 22,48,49 . Further, the FDA's policy of using class labeling for estrogen-containing products does not allow for accurate differentiation between the risks associated with systemic estrogen therapies and low-dose vaginal therapies, leading to overestimation of risk associated with low-dose vaginal therapies and avoidance of highly effective treatment for GSM by many women.…”
Section: How Do We Close the Menopause Care Gap?mentioning
confidence: 99%